Plasma gasification of refuse derived fuel in a single-stage system using different gasifying agents - Agon, N; Hrabovský, M; Chumak, O; Hlína, M; Kopecký, V; Masláni, A; Bosmans, A; Helsen, L; Skoblja, S; Van Oost, G; Vierendeels, J (Waste management, 2016)
The renewable evolution in the energy industry and the depletion of natural resources are putting pressure on the waste industry to shift towards flexible treatment technologies with efficient materials and/or energy recovery. In this context, a thermochemical conversion method of recent interest is plasma gasification, which is capable of producing syngas from a wide variety of waste streams. The produced syngas can be valorized for both energetic (heat and/or electricity) and chemical (ammonia, hydrogen or liquid hydrocarbons) end-purposes. This paper evaluates the performance of experiments on a single-stage plasma gasification system for the treatment of refuse-derived fuel (RDF) from excavated waste. A comparative analysis of the syngas characteristics and process yields was done for seven cases with different types of gasifying agents (CO2+O2, H2O, CO2+H2O and O2+H2O). The syngas compositions were compared to the thermodynamic equilibrium compositions and the performance of the single-stage plasma gasification of RDF was compared to that of similar experiments with biomass and to the performance of a two-stage plasma gasification process with RDF. The temperature range of the experiment was from 1400 to 1600 K and for all cases, a medium calorific value syngas was produced with lower heating values up to 10.9 MJ/Nm(3), low levels of tar, high levels of CO and H2 and which composition was in good agreement to the equilibrium composition. The carbon conversion efficiency ranged from 80% to 100% and maximum cold gas efficiency and mechanical gasification efficiency of respectively 56% and 95%, were registered. Overall, the treatment of RDF proved to be less performant than that of biomass in the same system. Compared to a two-stage plasma gasification system, the produced syngas from the single-stage reactor showed more favourable characteristics, while the recovery of the solid residue as a vitrified slag is an advantage of the two-stage set-up.
Keywords: Refuse Disposal; odpadky - odstraňování; Gases; plyny; tuhý odpad; biomasa; plazmové plyny; Biomass; Plasma Gases; Solid Waste